Motion sickness, nausea and thermoregulation: The “toxic” hypothesis - Nalivaiko, Eugene (Temperature (Austin), 2014)
Principal symptoms of motion sickness in humans include facial pallor, nausea and vomiting, and sweating. It is less known that motion sickness also affects thermoregulation, and the purpose of this review is to present and discuss existing data related to this subject. Hypothermia during seasickness was firstly noted nearly 150 years ago, but detailed studies of this phenomenon were conducted only during the last 2 decades. Motion sickness-induced hypothermia is philogenetically quite broadly expressed as besides humans, it has been reported in rats, musk shrews and mice. Evidence from human and animal experiments indicates that the physiological mechanisms responsible for the motion sickness-induced hypothermia include cutaneous vasodilation and sweating (leading to an increase of heat loss) and reduced thermogenesis. Together, these results suggest that motion sickness triggers highly coordinated physiological response aiming to reduce body temperature. Finally, we describe potential adaptive role of this response, and describe the benefits of using it as an objective measure of motion sickness-induced nausea.